OPTIMASI PENJUALAN LAPTOP ASUS DAN ACER DENGAN METODE SIMPLEKS - Deka Agustina; Bambang Sri Anggoro; Dian Anggraini (Unisda Journal of Mathematics and Computer Science (UJMC), 2018)
Linear Programming or Linear Program is a way in mathematics that is used to solve optimization problems in industry, banking, education, and problems that can be expressed in linear form. One of the settlement methods that can be used in Linear Programming is the simplex method. This study aims to get the best model for sales of Asus and Acer laptops with simplex method. The result of this research is the most optimal model that is in the fifth model with the optimum result 1032751 units per year then done the comparison with optimum result of year 2017 the result is not much different.